1967
DOI: 10.1172/jci105681
|View full text |Cite
|
Sign up to set email alerts
|

A Study of the Mechanisms by Which Adrenocorticotropic Hormone Maintains Adrenal Steroidogenic Responsiveness*

Abstract: Abstract. Following hypophysectomy in the rat, there was a progressive decline in the rate of adrenal protein synthesis in vivo during the ensuing 24-48 hr, and an accompanying decrease in the acute corticosterone secretory response to an intravenous injection of ACTH. There was a similar decrease in the in vitro conversion of A5-pregnenolone, progesterone, and deoxycorticosterone to corticosterone. These in vivo and in vitro effects of hypophysectomy could be reversed by the administration of depot ACTH for a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
10
0

Year Published

1968
1968
2008
2008

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(11 citation statements)
references
References 16 publications
1
10
0
Order By: Relevance
“…In the absence of ACTH free adrenal cholesterol presumably returns to plasma in an unmetabolized form whereas under the influence of ACTH a major fraction (see below) is first diverted towards the pathways of steroid hormone synthesis. This concept is compatible with the known mode of action of ACTH which accelerates the conversion of adrenal cholesterol into A5-pregnenolone and of A5-pregnenolone into steroid hormones (11,44). It also confirms and explains the experimental observations by Sayers, Sayers, Frey, White, and Long (40) who showed that hypophysectomized rats are still capable of replenishing depleted stores of adrenal cholesterol.…”
Section: Parameters Of Adrenal Cholesterol In Control Studiessupporting
confidence: 87%
“…In the absence of ACTH free adrenal cholesterol presumably returns to plasma in an unmetabolized form whereas under the influence of ACTH a major fraction (see below) is first diverted towards the pathways of steroid hormone synthesis. This concept is compatible with the known mode of action of ACTH which accelerates the conversion of adrenal cholesterol into A5-pregnenolone and of A5-pregnenolone into steroid hormones (11,44). It also confirms and explains the experimental observations by Sayers, Sayers, Frey, White, and Long (40) who showed that hypophysectomized rats are still capable of replenishing depleted stores of adrenal cholesterol.…”
Section: Parameters Of Adrenal Cholesterol In Control Studiessupporting
confidence: 87%
“…nous A5-pregnenolone, progesterone, or deoxycorticosterone, the formation of corticosterone is increased (20). To test whether the adrenocortical carcinoma could also perform this series of reactions, tumor tissue was incubated with exogenous A5-pregnenolone or progesterone, and it was found that corticosterone production was enhanced (Table IV).…”
Section: Resultsmentioning
confidence: 99%
“…It is positioned centrally within the hypothalamic-pituitary-adrenal (HPA) axis: stress leads to release of corticotropin-releasing factor (CRF) from the hypothalamus, which in turn stimulates corticotroph cells of the anterior pituitary to release ACTH, which stimulates the adrenal to produce corticosterone. Production of corticosterone then negatively regulates the release of CRF in a feedback loop to the hypothalamus.At the molecular level, ACTH has been shown to regulate many, if not all, of the factors involved in adrenal corticosteroidogenesis, among them the receptors which mediate uptake of cholesterol into the cell, the enzymes which mediate conversion of cholesterol esters to free cholesterol and translocation into mitochondria, as well as the mitochondrial enzymes converting cholesterol to corticosterone (7,8,17,18,33). Regulation of these factors was assessed at the gene or protein level either by adding ACTH to in vitro systems such as primary cell cultures from human, bovine, rat, and mouse adrenals, as well as the Y1 tumor adrenal cell line (10,23,27,28,30,31), or by removing ACTH in vivo through hypophysectomy of rats (16,18,29).…”
mentioning
confidence: 99%
“…Regulation of these factors was assessed at the gene or protein level either by adding ACTH to in vitro systems such as primary cell cultures from human, bovine, rat, and mouse adrenals, as well as the Y1 tumor adrenal cell line (10,23,27,28,30,31), or by removing ACTH in vivo through hypophysectomy of rats (16,18,29). The resulting effects demonstrate either the potential of ACTH to regulate a particular factor (in vitro experiments) or the reaction of intact adrenals to the sudden depletion of ACTH (in vivo experiments).…”
mentioning
confidence: 99%